Application of fish hydrolyzate to reduce feed requirements and improve the health of broiler chickens - Lelono, Asmoro; Sjaifullah, Achmad (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2023)
Feed management, which accounts for 70% of overall production expenses, is one of the cornerstones of effective broiler chicken farming. The body weight, health, and nitrogen levels in faeces can all be improved by adding additives to feed. This community service's goal is to guide and support broiler chicken breeders in their usage of fish hydrolyzed for feed management. This activity was carried out in August and September 2023 in the chicken farming partner owned by Mrs. Cholili's with a production capacity of up to 20,000 in Mumbulsari village, Mumbulsari district, Jember Regency. The methods are counselling, feeding practices and assistance during the production phase. The outcome is mastering the technique for adding fish hydrolyzed to enhance the health and growth performance of chickens. This skill and knowledge could be implemented by other farmers to maximize yields by using fish hydrolyzate.